Financing Entrepreneurial Firms in Europe: Facts, Issues, and Research Agenda - Laura Bottazzi; Marco da Rin (Center for Economic Studies and ifo Institute (CESifo), 2003)
During the latter part of the 1990s the introduction of the euro, the dramatic increase in the supply of venture capital in most EU countries, and the creation of several new' equity markets targeted at innovative firms have dramatically transformed the financing prospects of European entrepreneurial firms. In this study we contribute to a deeper understanding of their actual relevance by (i) gathering new evidence on European venture capital and on Europe's new' stock markets, (ii) providing a rigorous econometric analysis of their impact on corporate growth, and (iii) elaborating on our findings to devise a research agenda.
Keywords: 330; venture capital; initial public offerings (IPOs); entrepreneurship; going public; accounting standards